Analyzing Earnings Response Coefficient - s, Putri Irene; Djajanti, Atik (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study examines how capital structure, default risk, and earnings volatility affect the Earnings Response Coefficient (ERC) of property and real estate firms listed on the Indonesia Stock Exchange (BEI) from 2019 to 2024, with profitability as a moderating factor. Design/methodology/approach: The study included 92 property and real estate companies and used quantitative correlational and causal-associative analysis. Purposive sampling selected 17 firms. Secondary data came from the Indonesian Capital Market Directory (ICMD) and BEI website yearly financial statements. Analytical testing was done using PLS-SEM with SmartPLS 3.0 to examine putative relationships. Findings: When well-managed, elevated debt-to-equity ratios and default risks boost the market's reaction to earnings announcements, positively affecting ERC. Earnings volatility had a negative but statistically negligible effect, suggesting market participants see such variations as normal for the sector. Profitability reduces the negative effects of capital structure, default risk, and earnings volatility on ERC. Profitability boosts investor confidence in earnings reliability, increasing ERC responsiveness. Paper type: a Research Paper